Multifunctional-high resolution imaging plate based on hydrophilic graphene for digital pathology. (10th December 2022) - Lee, Geonhee; Oh, Yuna; Nam, Jung Tae; Ji, Seulgi; Jang, A-Rang; Jeong, Du Won; Kang, MinSoung; Lee, Sun Sook; Chae, Soosang; Cho, Donghwi; Hwang, Jun Yeon; Lee, Kyungeun; et al.
Abstract: In the present study, we showed that hydrophilic graphene can serve as an ideal imaging plate for biological specimens. Graphene being a single-atom-thick semi-metal with low secondary electron emission, array tomography analysis of serial sections of biological specimens on a graphene substrate showed excellent image quality with improved z -axis resolution, without including any conductive surface coatings. However, the hydrophobic nature of graphene makes the placement of biological specimens difficult; graphene functionalized with polydimethylsiloxane oligomer was fabricated using a simple soft lithography technique and then processed with oxygen plasma to provide hydrophilic graphene with minimal damage to graphene. High-quality scanning electron microscopy images of biological specimens free from charging effects or distortion were obtained, and the optical transparency of graphene enabled fluorescence imaging of the specimen; high-resolution correlated electron and light microscopy analysis of the specimen became possible with the hydrophilic graphene plate.